2018
DOI: 10.1002/cplu.201800534
|View full text |Cite
|
Sign up to set email alerts
|

Photocurrent Response and Progesterone Degradation by Employing WO3 Films Modified with Platinum and Silver Nanoparticles

Abstract: The effect of silver (Ag 0 ) and platinum (Pt 0 ) metallic nanoparticles (NPs) on WO 3 film was investigated by studying the photocurrent response under polychromatic irradiation. The structural phase revealed by X-ray diffraction analysis indicates a monoclinic crystal nanostructure. WO 3, Ag 0 /WO 3, and Pt 0 /WO 3 electrodes were used to degrade 0.35 mg L À 1 progesterone hormone in aqueous solution under polychromatic irradiation for 3h. The studies on degradation were investigated under electrochemically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…It can be observed that most of the studies focus on analyzing PGT removal using HPLC technique that mostly indicates the transformation of PGT to other compounds and not its complete degradation. Application of photocatalysis was found to be incapable of complete degradation of PGT [13,14]. The only study that discussed the application of electrochemical advanced oxidation process (EAOP) concentrated on removing water soluble combination of PGT that is different from its synthetic form sold as medication.…”
Section: Sl No Locationmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that most of the studies focus on analyzing PGT removal using HPLC technique that mostly indicates the transformation of PGT to other compounds and not its complete degradation. Application of photocatalysis was found to be incapable of complete degradation of PGT [13,14]. The only study that discussed the application of electrochemical advanced oxidation process (EAOP) concentrated on removing water soluble combination of PGT that is different from its synthetic form sold as medication.…”
Section: Sl No Locationmentioning
confidence: 99%
“…The usage of costly conductive diamond electrodes for EAOP further limited its wide scale application [15,16]. Further, removal studies on PGT are limited compared to other steroid contaminants such as estradiol and testosterone [14,15].…”
Section: Sl No Locationmentioning
confidence: 99%
“…Photovoltages of various photoanodes made up of BiVO 4 , Fe 2 O 3 , Cu 2 O, and WO 3 reported from the previous studies.…”
mentioning
confidence: 99%
“…Consequently, BiVO 4 and other metal oxides exhibit considerably lower performances in comparison to what is anticipated from the Schottky-Queisser limit. Figure shows the performances of metal oxide photoelectrodes in terms of photovoltage reported from the previous studies on BiVO 4 , Fe 2 O 3 , Cu 2 O, and WO 3 . The photovoltages are estimated from the difference between the onset potentials where PEC devices begin to generate the current density from a targeted electrochemical reaction (HER for photocathode and OER for photoanode) and redox potential of the electrochemical reactions (0 V vs RHE for HER and 1.23 V vs RHE for OER). Although the performances of the metal oxide photoanode have significantly improved, there are still large discrepancies between the theoretical limit.…”
mentioning
confidence: 99%